POLITIK UANG DALAM PEMILUKADES DESA CANGKRING DAN DESA DAWUAHAN, KECAMATAN TALANG, KABUPATEN TEGAL 2012 - Fuji Hastuti; Wiwik Widayati; Priyatno Harsasto (Journal of Politic and Government Studies, 2013)
Money politics was one of violation within Pemilukades, cause influence weaken democracy value. Money politics was all of gift such or goods from such candidate to the voters in order to influence voters. Money politics pattern occurred was vary and variation.This research, used descriptive research method. Location tkis research in Tegal Regency, appropriately subdistrict, Tegal, cangkring and Dawuhan.sample collection technique used purposive sampling. Data collection tectique used primary data, it was interview with informant and secondary data was collection which refer to written resource.This research found thah money politics already became tradition  for society of Cangkring and Dawuhan village, money politics occurred were related to lack of by mentality. Slogan of “laka duit laka acara nyoblos” it meant “no money, no vote” pattern  occours include : 1) candidancy 2)build campaign teams 3) campagn of “serangan fajar” 4) type money politics (money and goods)Based on research result above. In order to descending money politics practice government needs socialization about money politik risk. Besides thah, money politik practive couls descended significantly, when Indonesia society have anough education.